Automated Financial Management System: A Case Study of Batuma’s Dairy Farm. - Kesande, Blendah; Nahwera, Praise (Kabale University, 2024)
This study investigated the automated financial management system of Batuma's dairy farm in the Bubaare sub-county Rubanda district along Kabale-Kisoro road. The main objective of the study was to develop an automated financial management system tailored to the specific needs of dairy farms in Uganda. The study had other specific objectives which included; Designing an Automated Financial Management System, Implementing the Automated Financial Management System, and testing and validating the Automated Financial Management System. Three research questions were raised in line with the objectives of the study. The first one was; How can an Automated Financial Management System be effectively designed to address the identified issues with the current manual systems? What are the key considerations and challenges involved in the implementation of an Automated Financial Management System within the context of the dairy farm in Uganda?, the last one was; How can the designed Automated Financial Management System be rigorously tested and validated to ensure its effectiveness in improving financial management processes for dairy farm?. This study was conducted in Batuma's dairy farm office in different departments like: Board and legal, customs and exercise, domestic taxes, corporate services, internal audit and compliance, and tax investigation. Data was obtained from managers and assistants, secretaries, and other concerned employees. An interview guide and observation guide were used as project research tools to collect data in the dairy farm. The finding of the study revealed that the system being used was not sufficient and effective; this included inadequate database retrieval and poor record analysis and comparison.